Islamic Education in Malaysia: A Study of History and Development - Ishak, Mohd. Shuhaimi; Abdullah @ Chuah Hock Leng, Osman (ROUTLEDGE, 2013)
Abstract Before independence, the British promoted a Malay vernacular education with some form of Islamic education. This gave rise to what is popularly known as the dichotomy of education into secular and religious streams. The Malaysian government later made an effort for the reintroduction of Islamic education and in the 1970s implemented the New Economic Policy. Under the policy, the government realized the importance of Islamic education in affirming Malay hegemony. The study attempts to shed light on the variety of forms, patterns, and evolutionary trends of Islamic education and hopefully present a more subtle picture of the Malaysian Islamic education.